2013
DOI: 10.6000/1927-3037.2013.02.03.2
|View full text |Cite
|
Sign up to set email alerts
|

MarA, SoxS and Rob of Escherichia coli – Global Regulators of Multidrug Resistance, Virulence and Stress Response

Abstract: Bacteria have a great capacity for adjusting their metabolism in response to environmental changes by linking extracellular stimuli to the regulation of genes by transcription factors. By working in a co-operative manner, transcription factors provide a rapid response to external threats, allowing the bacteria to survive. This review will focus on transcription factors MarA, SoxS and Rob in Escherichia coli, three members of the AraC family of proteins. These homologous proteins exemplify the ability to respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
118
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(122 citation statements)
references
References 218 publications
(326 reference statements)
4
118
0
Order By: Relevance
“…Expression of the AraC/ XylS family member SoxS has been described to be activated in response to oxidative stress in E. coli and other enterobacteria (15). In the present study, we demonstrated that SoxS from E. amylovora Ea1189 is also involved in superoxide resistance.…”
Section: Figsupporting
confidence: 54%
See 2 more Smart Citations
“…Expression of the AraC/ XylS family member SoxS has been described to be activated in response to oxidative stress in E. coli and other enterobacteria (15). In the present study, we demonstrated that SoxS from E. amylovora Ea1189 is also involved in superoxide resistance.…”
Section: Figsupporting
confidence: 54%
“…Many genes are under either local or global transcriptional control. For example, the multidrug transporter AcrAB is locally controlled by the transcriptional repressor AcrR in Escherichia coli (10,11) and Salmonella enterica (12) and by global transcriptional activators of the AraC/XylS family, such as MarA, SoxS, and Rob (13)(14)(15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of the role played by MgrA toward tetR21 expression was not clear, since a lack of MgrA did not lead to an obvious change in the level of tetR21 expression in either direction. Many multidrug efflux pumps in Gram-negative bacteria like E. coli, K. pneumoniae, and E. cloacae are controlled by special regulatory systems that mediate responses to hostile environments (37). In addition, studies of Gram-negative efflux pumps revealed that the expression of several transporters of the RND (resistance-nodulation-division) family of multidrug (MDR) transporters were induced by and transported cellular metabolites as part of the bacterial cell physiology (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…T ranscription factors of pathogenic bacteria can be important virulence determinants, since they control genes that specify toxins, proteins functioning in nutrient acquisition within the hostile host environment, and products that operate by subverting the host innate immunity (1)(2)(3)(4). For example, in Bacillus anthracis, the causative agent of the zoonotic infectious disease, anthrax, the plasmid-borne atxA gene encodes a transcription factor required for virulence, since it is necessary for the activation of genes for toxin and protective capsule production (5,6).…”
mentioning
confidence: 99%